Islamic Education as an Approach to Drug Rehabilitation - Intan Afriaty (el-Tarbawi : Jurnal Pendidikan Agama Islam, 2024)
Drug abuse is a serious problem that affects individuals and society. drug rehabilitation that requires a holistic and spiritual approach as pe cts. This research group aims to re-explore the role of rat education as a drug rehabilitation approach. There is research on the methods used by researchers by collecting data from all observations, parts of observations, and required documents. There are findings that show that Islamic education is very important for the recovery process of illegal drug patients. This is an educational program that must be carried out which includes enthusiasm, morals, and so on. The research results showed that patients responded positively to Islamic religious education through approaches, attitudes, values ​​and behavior. The approach I take is about how to recover and recover from past drugs. . Implementation of this research is necessary to integrate Islamic education into Drug Addiction programs, provide speed to this approach, and I will not return our organization to support patient recovery.